Avaliação da solubilidade da curcumina e caracterização de filme ativo incorporado com nanosuspensão de curcumina - Carvalho, Deivis de Moraes (2014)
Curcumin is a yellow antifungal, bioactive agent and natural antioxidant compound obtained from Curcuma rhizomes. It presents the disadvantage of low solubility in water. Nanocurcumin can be more soluble than curcumin. Surfactants can also be applied to increase substances solubility and prevent particle aggregation. Active packaging systems are based on materials with additives to be added to the polymer in order to extend shelf life and increase consumer safety. The physical properties of the polymers are associated with the addition and miscibility of components. Mechanical analyses are generally carried out on active packaging to verify handling resistance, flexibility and elasticity as well as the efficiency of food protection. The objectives of this study we pre: to increase curcumin solubility; to assess the antioxidant activity; to produce an active film with addition of curcumin nanosuspension; to assess the active component physical characteristics and migration. Curcumin proved more soluble in glycerol and ethanol than in water and more soluble in ethanol than in glycerol. Meaningful increase was observed in curcumin solubility for these solvents mixture compared with pure water. The method applied to decrease the particles size proved efficient. Curcumin suspensions in tween 80 increased solubility. Curcumin presented good antioxidant activity. The decrease in particles size did not increase curcumin antioxidant activity. The addition of curcumin influenced the mechanical characteristics of the cellulose acetate films but did not affect the CO2 permeability. Curcumin provided the films with yellow coloring and increased their opacity. No meaningful difference was observed for the rate of migration between nanosuspension and a simple mixture of curcumin and tween 80. The curcumin migration was higher for the films with tween 80 addition.